2017
DOI: 10.1007/s00261-017-1207-3
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis of FDG PET/CT for differentiating between FDG-avid benign and metastatic adrenal tumors: efficacy of combining SUV and texture parameters

Abstract: The combined use of SUV and texture parameters has a potential to significantly increase the diagnostic performance to differentiate between large FDG-avid BATs and MATs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 30 publications
2
17
0
2
Order By: Relevance
“…A recently performed meta-analysis indicated that the level of evidence is low to very low for all these imaging methods (151). In the last 2 years, some additional studies have been published (159,160,161,162,163,164,165,166,167,168,169,170,171,172). However, the panel still considers that of the available imaging modalities, only non-contrast CT is sufficiently reliable to rule-out an ACC when the adrenal lesion is homogenous and has low CT density ≤10 HU.…”
Section: Reasoningmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently performed meta-analysis indicated that the level of evidence is low to very low for all these imaging methods (151). In the last 2 years, some additional studies have been published (159,160,161,162,163,164,165,166,167,168,169,170,171,172). However, the panel still considers that of the available imaging modalities, only non-contrast CT is sufficiently reliable to rule-out an ACC when the adrenal lesion is homogenous and has low CT density ≤10 HU.…”
Section: Reasoningmentioning
confidence: 99%
“…In contrast, ACCs are usually large and of inhomogeneous appearance and characterized by low fat content (and hence higher HU density) (173). Recently, FDG-PET has been proposed as possibly the best secondline test to assess indeterminate masses by unenhanced CT (159,165,166). However, the experience shows that sensitivity and negative predictive value are much better than specificity or positive predictive value.…”
Section: Reasoningmentioning
confidence: 99%
“…These features quantify image intensity, shape, and texture and may be of added value to traditionally clinico-pathological reports. Numerous recent studies have demonstrated that CT and/or 18 F-FDG PET radiomics can outperform conventional radiological measurements in the prediction of γpCR in esophageal cancer patients [6][7][8][9][10][11][12][13][14][15]. Nevertheless, the use of radiomic features as quantitative image biomarkers requires further optimization and improvement in order to achieve routine clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Textural feature analysis increases the information retrievable from PET/CT images, which is useful for characterizing and classifying tissue and lesions according to differences in morphology [2]. Adding texture analysis to a PET/CT readout can thus improve diagnostic sensitivity and specificity for certain tumor entities [3]. Notably, textural features are exploited as a surrogate measure of tissue metabolic heterogeneity [4], which can be an index of tumor malignancy, for example in the case of thymic epithelial cancer [5].…”
Section: Introductionmentioning
confidence: 99%